Предмет: Алгебра,
автор: Sanek5552
Решите все 3 задания плиииз
Приложения:
Ответы
Автор ответа:
0
3) y - (3x² - x) = 5x² - 6x
y = 5x² - 6x + 3x² - x = 8x² - 7x
Уменьшаемое равно 8x² - 7x
4a) 2x(a - b) + a(a - b) = (a - b)(2 + a)
4б) 3x + 3y - bx - by = (3x + 3y) - (bx + by) = 3(x + y) - b(x + y) = (x + y)(3 - b)
5) 4x * 3x - (3x - 19)(2x + 4) = 12x² - 6x² - 12x + 38x+ 76 = 6x² + 26x + 76
y = 5x² - 6x + 3x² - x = 8x² - 7x
Уменьшаемое равно 8x² - 7x
4a) 2x(a - b) + a(a - b) = (a - b)(2 + a)
4б) 3x + 3y - bx - by = (3x + 3y) - (bx + by) = 3(x + y) - b(x + y) = (x + y)(3 - b)
5) 4x * 3x - (3x - 19)(2x + 4) = 12x² - 6x² - 12x + 38x+ 76 = 6x² + 26x + 76
Похожие вопросы
Предмет: Қазақ тiлi,
автор: IaBober
Предмет: История,
автор: arturbotasev6
Предмет: Английский язык,
автор: elenaeftifeeva4
Предмет: Геометрия,
автор: кирилл1346